Community perceptions, knowledge, and coping mechanisms concerning perennial climate change-related disasters along the Volta estuary of Ghana, West Africa - Mattah, M.M.; Mattah, P.A.D.; Mensah, A.M.; et al. (Scientific African, 2024)
Communities along the Volta estuary of Ghana remain vulnerable to perennial tidal wave attacks, coastal erosion, and flooding because of increasing sea level rise from climate change. Using both qualitative and quantitative methods, community knowledge, and perceptions on disasters and disaster risks were explored. We also investigated perceived factors contributing to increase di sasters, how communities’ knowledge and perceptions informed their preparedness and response to the disasters. Focus group discussions, key informant interviews and households survey were conducted in nine selected communities from two adjoining districts located immediate east and west of the Volta estuary. Results indicated that communities were knowledgeable about the perennial climate change-related disasters occurring in their districts. A z-test conducted on the respondents’ knowledge of key environmental threats revealed significant variations between the two districts. With much experience, households were able to tell when a weather phenomenon could be disastrous. Households over the years have devised various strategies to predict, cope with and reduce the effects of disasters. Some strategies for predicting the occurrence of disasters included watching the size and position of the moon, watching for, and listening to the chirps of certain birds and observing the patterns presented by clouds in the sky. Other strategies for coping with disasters include reliance on social capital to support the vulnerable in society as well as migrating out of the study areas. Overall, 53.5 % of the households interviewed confirmed that between one (1) and four (4) members of their households had migrated to other places in Ghana and outside the country. The study concluded that communities in disaster-prone areas have good knowledge of their environment and should therefore be collaborated with to reduce the impact of disasters as stated in the Sendai Framework.
Research Aricle
Keywords: Understanding disasters; Disaster risk reduction; Estuary